Recognised anomalies of corpus callosum: clinical spectrum and associated malformations—a single-centre experience. (29th September 2015) - Mulay, K; Corry, P; Wildig, K; Yeung, S
Abstract : Background: The corpus callosum plays a pivotal role in the inter-hemispheric transfer and integration of information. Agenesis of the corpus callosum is a frequently recognised anomaly that may present with a wide spectrum of clinical features. Objectives: To characterise the demographic profile, clinical phenotypes, describe the associated malformations and to evaluate long-term outcomes including neurodevelopment in children with anomalies of the corpus callosum. Methods: A retrospective case-note review of children with documented agenesis/dysgenesis of the corpus callosum attending the Child Development Centre (neurodisability service) at St. Luke's Hospital, Bradford, UK, between 1990 and 2008 was performed. Results: Forty-six children (32 boys) with a median age of 7 years (range: 2 months–17.5 years), the majority being of South Asian origin and born of consanguineous marriages, were identified. More than two-thirds of the patients were identified in the neonatal period (before 4 weeks of age) and the overwhelming majority (96%) in infancy. Four-fifths of patients had other associated malformations of the central nervous system (CNS). Non-central nervous system malformations were seen in 85%. More than a third of children suffered from epilepsy, the majority requiring monotherapy to control their seizures. Global developmental delay was seen in 93%. Associated chromosomal anomalies, syndromes and metabolic disorders were identified only in a minority. A small number of children also presented with behavioural and neuropsychiatric problems including autistic spectrum disorder. Conclusion: The neurodevelopmental outcome in children with callosal abnormalities to a great extent depends on the presence and the severity of associated CNS malformations. Future studies are needed to justify the role of fetal MRIs to help diagnose these anomalies and formulate an appropriate multidisciplinary management plan.